2014
DOI: 10.1007/s11033-014-3630-7
|View full text |Cite
|
Sign up to set email alerts
|

The combined QF-PCR and cytogenetic approach in prenatal diagnosis

Abstract: In this study, the importance of quantitative fluorescence polymerase chain reaction (QF-PCR) aneuploidy diagnosis test which provides earlier and easier results were discussed. The cell cultures and DNA isolations were performed on 100 amniotic fluids. DNA isolations were made from peripheral blood samples of mothers who had blood-stained amniotic fluid samples. The reasons of references of these pregnant women to our division were increased maternal age, positive double/triple screening test and fetal anomal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 21 publications
2
15
1
Order By: Relevance
“…Rostami et al 12 reported 4,058 samples analyzed for QR-PCR with a detection rate of 98.59%. Tekcan et al 18 compared 100 amniotic fluid samples with karyotype results and obtained 99% concordance on 100 samples, including 4 abnormalities. These three authors reported higher detection rates than in our study; however, the percentages of total chromosomal abnormalities in these studies were 7.6% and 4.1%, respectively, whereas in the current study, approximately half of the population was abnormal.…”
Section: Discussionmentioning
confidence: 99%
“…Rostami et al 12 reported 4,058 samples analyzed for QR-PCR with a detection rate of 98.59%. Tekcan et al 18 compared 100 amniotic fluid samples with karyotype results and obtained 99% concordance on 100 samples, including 4 abnormalities. These three authors reported higher detection rates than in our study; however, the percentages of total chromosomal abnormalities in these studies were 7.6% and 4.1%, respectively, whereas in the current study, approximately half of the population was abnormal.…”
Section: Discussionmentioning
confidence: 99%
“…In one of those studies, a cytogenetic result could be obtained in 98.8% of the 6124 cases evaluated by using AC [24]. In another study the culture success rate was 99% [25]. However, these studies reported only amniocentesis data.…”
Section: Discussionmentioning
confidence: 99%
“…Rostami et al [8] reported 4058 samples analyzed for QF-PCR with a concordance of 98.59%. Tekcan et al [9] compared 100 amniotic fluid samples with karyotype results and obtained 99% concordance on 100 samples, including 4 abnormalities. More recently, Sun et al also found QF-PCR was comparable to conventional cytogenetic testing [10].…”
Section: Discussionmentioning
confidence: 99%